Description Of Sleep Quality Of Patients With Chronic Obstructive Pulmonary Disease (COPD) Who Were Treated In The Jasmine Room At The Arifin Achmad Regional General Hospital Riau Province - Ulfa Hasana; Asniati Asniati (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
Various Lung Diseases will still be a public health problem. COPD or Chronic Obstructive Pulmonary Diseases (COPD) is a disease characterized by partially reversible and progressive inhalation flow obstruction associated with an abnormal inflammatory response from the lungs to exposure to harmful particles or gases (Black, JM & Hawk, JH 2014). Respiratory disease generally affects sleep, especially clients with chronic lung disease such as emphysema with clinical symptoms of short breathing. Most COPD patients report that their sleep is often disturbed due to shortness of breath, coughing and excessive secretion production, especially at night. The study design used was descriptive. The population in this study were COPD patients in the jasmine room at Arifin Achmad Hospital, Riau province. Sampling was taken by purposive sampling as many as 30 respondents. The instrument in this study to assess the quality of the bed using the PSQI questionnaire. The results showed that the sleep quality of lung disease patients treated in the jasmine room at Arifin Achmad Hospital was in the bad category, namely 23 people (77%). This research is expected to be a reference in providing nursing interventions for COPD sufferers who experience sleep disorders